Mutual and Thermal Diffusivities in Binary Mixtures of n-Hexane or 1-Hexanol with Krypton, R143a, or Sulfur Hexafluoride by Using Dynamic Light Scattering and Molecular Dynamics Simulations - Piszko, Maximilian; Lenahan, Frances; Dennstädt, Claudio; Klein, Tobias; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2023)
This work reports Fick diffusion coefficients D11 in the saturated liquid phase(s) of binary mixtures of nonpolar n-hexane (n-C6H14) or polar 1-hexanol (1-C6H14O) with dissolved krypton (Kr), 1,1,1-trifluoroethane (R143a), or sulfur hexafluoride (SF6). Investigations were performed at temperatures T of 303, 323, and 348 K and gas mole fractions up to 0.999. The comparison between Kr and R143a, both having nearly the same molar mass, allows identification of the impact of molecular structure and polarity of the dissolved gas on D11. The investigation of SF6 provides information about the influence of a centrosymmetric molecule with a large molar mass on D11. D11 is experimentally determined by dynamic light scattering (DLS) and predicted by equilibrium molecular dynamics (EMD) simulations by the independent calculation of the Maxwell-Stefan diffusivity and the thermodynamic factor Γ11 in macroscopic thermodynamic equilibrium at or close to saturation conditions. Thermal diffusivity data obtained simultaneously with D11 by DLS are reported as well. The behavior of the experimentally determined D11 as a function of composition and that obtained from EMD simulations show generally good agreement. Distinct structural changes of the saturated liquid phase are reflected by the change of Γ11 which extends for the present study between 0.16 and 1.3. While for mixtures of 1-C6H14O + Kr, D11 as a function of composition is nearly constant at a given T, all other mixtures show a distinct composition-dependent behavior. For mixtures of 1-C6H14O + R143a and 1-C6H14O + SF6, a strong slowing down of D11 was observed and related to approaching a liquid-liquid miscibility gap. For all systems, the behavior of D11 as a function of composition is interpreted with reference to the fluid structure accessible by EMD.
CRIS-Team Scopus Importer:2023-06-30